Cortical auditory evoked potentials in cochlear implant listeners via single electrode stimulation in relation to speech perception - Liebscher, Tim; Alberter, Katrin; Hoppe, Ulrich (International Journal of Audiology, 2018)
The objectives of this study were to investigate the effects of place of stimulation on cortical auditory evoked potentials in relation to speech performance in cochlear implant listeners. It was designed that cortical responses were recorded for single-electrode bursts at apical, medial and basal portions of the electrode array with varying inter-stimulus intervals ranging from 300 ms to 5 s. Latency and amplitude of N1 and P2 peaks were analysed in relation to monosyllabic word scores. The study sample was 44 adult cochlear implant users ranging in age from 28 to 86 years. N1, P2 and N1-P2 amplitudes declined significantly from apical to basal electrodes. The most robust and pronounced responses were recorded for slower stimulation rates (5 s). Speech recognition correlated positively with N1 and N1-P2 amplitudes at the medial electrode. P2 latency showed a significant negative correlation with speech performance at the apical electrode. At last, cortical responses varied significantly depending on the stimulation site and rate. We can objectively quantify speech performance with the N1, N1-P2 amplitude and P2 latency in cochlear implant users. Deafness-related neural degeneration persists even after the cochlear implantation and is more distinct at the base than the apex of the cochlea.
EVALuna2:35448